2023
DOI: 10.15587/1729-4061.2023.273934
|View full text |Cite
|
Sign up to set email alerts
|

Improving the method of linear-quadratic control over a physical model of vessel with azimuthal thrusters

Abstract: The object of this research is the algorithms for controlling large-scale models of sea-based vehicles (SBVs). The subject of the research is a linear-quadratic method for controlling a model of the propulsion complex with azimuthal thrusters (ATs) in the aft part. The problem is the solution between the interdependent throws of surge, sway, and yaw speeds predicted by the linear controller. Input signals are the rotational speeds and the angles of ATs propeller thrusts with respect to the diametrical plane of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…But experimental studies showed a certain discrepancy in the loss of optical power, calculated according to (8) and that obtained when testing a real OW (Fig. 1).…”
Section: Synthesis Of the Improved Mathematical Model Of Optical Powe...mentioning
confidence: 92%
See 2 more Smart Citations
“…But experimental studies showed a certain discrepancy in the loss of optical power, calculated according to (8) and that obtained when testing a real OW (Fig. 1).…”
Section: Synthesis Of the Improved Mathematical Model Of Optical Powe...mentioning
confidence: 92%
“…In work [8], it was assumed that the change in geometry or the reduction of oscillations by the supports of the azimuth propulsion device should be reflected in the total load transmitted by the propeller and the electric propulsion motor to the hull of the vessel. Therefore, it is advisable to use the results of the inclinometry of the supports of rowing electric motors as additional information on the stress and deformation of the hull.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation